Safety evaluation of the food enzyme containing endo‐polygalacturonase and β‐glucosidase from the non‐genetically modified Aspergillus tubingensis strain ARO - EFSA Panel on Food Enzymes (FEZ Panel); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme containing endo‐polygalacturonase and β‐glucosidase (EC 3.2.1.15 and EC 3.2.1.21) is produced with the non‐genetically modified Aspergillus tubingensis strain ARO by DSM Food Specialties B.V. The food enzyme was free from viable cells of the production organism. It is intended to be used in five food manufacturing processes. Dietary exposure was estimated to be up to 0.609 mg total organic solids (TOS)/kg body weight per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 2217 mg TOS/kg bw per day, the highest dose tested, resulting in a margin of exposure of at least 3640. A search for the homology of the amino acid sequence of the food enzymes to known allergens was made and four matches with food allergens and 22 matches with respiratory allergens were found. Known sources of food allergens were used in the food enzyme manufacturing process. The Panel considered that the risk of allergic reactions upon dietary exposure cannot be excluded. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.